Correlation of social support with the incidence of depression in orphaned adolescents living in orphanages - Arianti, Rizka; Isnaeni, Yuli (International Journal of Health Science and Technology, 2023)
Adolescence is an important period because it is a time when individuals seek self-identity and experience many problems. Depression is one of the biggest psychological disorders in adolescents, especially adolescents who by their keyatiman condition have to live in orphanages. This study aims to determine the relationship of social support with the incidence of depression in adolescents living in the Putri Aisyiyah Orphanage Yogyakarta, with a correlation design and cross-sectional time approach. Data was collected with questionnaires and analyzed with Spearman Rank. The results of this study showed that most adolescents in the Putri Aisyiyah Orphanage Yogyakarta received moderate social support as much as 23 (47.9%) and had a depression level in the category of not mild depression as many as 23 children (47.9%). The results of the Spearman Rank analysis found that the value of significance p = 0.000 means a significant relationship exists between social support and depression in adolescents living in the Putri Aisyiyah Orphanage Yogyakarta. It is therefore advisable for caregivers and orphaned adolescents to be able to increase social support, especially instrumental support both by caregivers and fellow adolescents in meeting material needs (finances and clothing) and support in solving personal problems and schoolwork.